APLIKASI ANALISIS KORESPONDENSI UNTUK MELIHAT KARAKTERISTIK USAHA PARIWISATA DI PROVINSI BALI - KUSUMA, AGUST WIRAS ARDI; SRINADI, I GUSTI AYU MADE; SARI, KARTIKA (E-Jurnal Matematika; Vol 5 No 2 (2016), 2016)
One of multivariate analysis application was used to see the relationship between two or more quantitative variable and objects within. Multivariate analysis which used in this case is correspondence analysis. This paper will be done correspondence analysis application in order to see the characteristic of tourism business in Bali. In this study it can be seen the characteristic of tourism business in Bali in a form of illustration of tourism business situation of each regencies which mapped in two dimensional plots. The result was Karangasem, Buleleng, Gianyar, Jembrana, Tabanan, and Klungkung were in a group because they have the same development of tourism area business and accommodation service business. However tourism business that was developed in Denpasar and Badung was tour and travel and food and beverage business .
Keywords: multivariate analysis; correspondence analysis; tourism business